1999
DOI: 10.1002/(sici)1096-9896(199909)189:1<12::aid-path431>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus is a necessary cause of invasive cervical cancer worldwide

Abstract: A recent report that 93 per cent of invasive cervical cancers worldwide contain human papillomavirus (HPV) may be an underestimate, due to sample inadequacy or integration events affecting the HPV L1 gene, which is the target of the polymerase chain reaction (PCR)‐based test which was used. The formerly HPV‐negative cases from this study have therefore been reanalysed for HPV serum antibodies and HPV DNA. Serology for HPV 16 VLPs, E6, and E7 antibodies was performed on 49 of the 66 cases which were HPV‐negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

68
4,356
10
308

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,716 publications
(4,742 citation statements)
references
References 26 publications
68
4,356
10
308
Order By: Relevance
“…In agreement with results reported in a nearby country having comparable socioeconomic status,16 our results indicated that the prevalence of HPV infection of any genotypes in Saudi CxCa patients (77%) is below the estimated worldwide range (85%‐99%) 3, 4, 17. Statistical analysis revealed that this rate is significantly lower than the lowest (85%) global estimation (1 sample z‐test; 95% CI, 71% ‐ 82%; P  = .001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with results reported in a nearby country having comparable socioeconomic status,16 our results indicated that the prevalence of HPV infection of any genotypes in Saudi CxCa patients (77%) is below the estimated worldwide range (85%‐99%) 3, 4, 17. Statistical analysis revealed that this rate is significantly lower than the lowest (85%) global estimation (1 sample z‐test; 95% CI, 71% ‐ 82%; P  = .001).…”
Section: Discussionsupporting
confidence: 91%
“…However, its incidence is not uniform in various populations having different socioeconomic and national human development levels; a large majority of the global burden occurs in less‐developed regions, and the lowest rates are in western Asia 1. Infection with human papillomavirus (HPV) stands out as being the main cause among all known risk factors, and high‐risk HPVs drive the major carcinogenic events in the pathogenesis of CxCa, with an estimated worldwide prevalence ranging between 85% and 99% 2, 3, 4. In contrast, CxCa incidence is low in a few countries, even though they lack national screening programs 5.…”
Section: Introductionmentioning
confidence: 99%
“…Although human papillomavirus (HPV) vaccines are available, cervical cancer still causes a considerable amount of death because of the limited application of the vaccine. Persistent infection with high‐risk HPV is the main aetiological factor in cervical carcinogenesis 2, 3, 4. However, HPV infection alone does not sufficiently explain the occurrence of cervical cancer because HPV oncogenes E6 and E7 can immortalize but do not transform human epithelial cells 5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 99.7% of CC cases worldwide showed the evidence of HPV infection 3. HPV‐16 and HPV‐18 are the most common HPV types detected in about 70% of global CC5 and 70.3% CC cases in Korea 2.…”
Section: Introductionmentioning
confidence: 99%